Modelling of kinetics of sulphur-containing compounds transformations in the process of hydrotreating - Krivtsova N. I. Nadezhda Igorevna; Tataurshchikov A. A. Anton Andreevich; Ivanchina E. D. Emilia Dmitrievna; Zanin I. K. Igor Konstantinovich (2016, 2016)
Title screen